2010
DOI: 10.1186/1471-2202-11-92
|View full text |Cite
|
Sign up to set email alerts
|

Automated quantitative gait analysis in animal models of movement disorders

Abstract: BackgroundAccurate and reproducible behavioral tests in animal models are of major importance in the development and evaluation of new therapies for central nervous system disease. In this study we investigated for the first time gait parameters of rat models for Parkinson's disease (PD), Huntington's disease (HD) and stroke using the Catwalk method, a novel automated gait analysis test. Static and dynamic gait parameters were measured in all animal models, and these data were compared to readouts of establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
113
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 39 publications
(49 reference statements)
11
113
2
3
Order By: Relevance
“…27 In the present study, we used CatWalk because this is more sensitive in measuring gait deficits in some animals than the rotarod test. 28 Using CatWalk, we found that chronically hyponatremic rats displayed findings similar to those seen in Purkinje cell-specific vesicular g-aminobutyric acid transporter knockout 29 or atm-deficient mice, 30 which exhibit cerebellar ataxia. The mechanisms underlying hyponatremia-induced gait abnormalities are currently unknown.…”
Section: Discussionmentioning
confidence: 79%
“…27 In the present study, we used CatWalk because this is more sensitive in measuring gait deficits in some animals than the rotarod test. 28 Using CatWalk, we found that chronically hyponatremic rats displayed findings similar to those seen in Purkinje cell-specific vesicular g-aminobutyric acid transporter knockout 29 or atm-deficient mice, 30 which exhibit cerebellar ataxia. The mechanisms underlying hyponatremia-induced gait abnormalities are currently unknown.…”
Section: Discussionmentioning
confidence: 79%
“…Here, we show that combination of memantine with rtPA is associated with better sensorimotor status (string test) and use of the plantar surface of the ipsilateral hind limb (CatWalk), a parameter also impaired in other cortical infarct models. 25 Memantine, as an individual treatment, is not effective in our thrombotic stroke model. These data are in agreement with the literature, because any beneficial effect of memantine alone was reported on a stroke model performed in healthy adult mice or rats when administrated after stroke onset.…”
Section: Discussionmentioning
confidence: 88%
“…The maximum contact area spatial parameter (ie, the maximum area of a paw in contact with the glass plate during the stance phase) was used as a measure of individual paw prints, as previously described. 25 The size of the right hind limb print was reduced (Ϫ27%) in delayed reperfused animals ( Figure 4A; saline versus late rtPA; PϽ0.05), whereas memantine alone did not improve the deficit measured in saline animals ( Figure 4A; saline versus late memantine; PϾ0.05). The coinjection of memantine with rtPA prevented the deleterious effects of late thrombolysis ( Figure 4A; late rtPA versus late memantine/rtPA; Pϭ0.05 and saline versus late memantine/ rtPA; PϾ0.05).…”
Section: Memantine Precludes the Deleterious Effects Of Delayed Thrommentioning
confidence: 97%
“…Each mouse was allowed three attempts to hold onto the inverted lid for an arbitrary maximum of 90 s, and the longest time was recorded. To evaluate motor coordination, we analyzed stride length for 14-wk-old mice with the use of a CatWalk apparatus (Noldus) (31). Each mouse was placed individually on the CatWalk walkway and allowed to traverse the glass plate of the walkway as many times as needed to obtain at least three fluent crossings in the dark.…”
Section: Methodsmentioning
confidence: 99%